Optimalisasi Strategi Peningkatan Mutu Pendidikan pada Era Revolusi Digital - Andriani, Rina; Umalihayati, Umalihayati; Oktaviani, Dwi Kania; Salam, Abdu; Novianti, Siti; Hamzah, Amaylia Rosyida; Amelia, Lesta; Nurmalita Sari, Amanda Prisilia; Zidha, Barrah Mariela; Alfermanda, Muhammad Naufal (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service activity was in the form of an educational seminar aimed at improving the quality of education, particularly teaching quality, in the digital era. The activity sought to enhance educational quality through teachers as the driving force, by implementing strategies and teaching methods adapted to the digital revolution, so that the quality of education in the region could improve sustainably. The method used consisted of preparation, implementation, evaluation, and reporting. The seminar was held at SD Lempuyang, Tanara Sub-district, on Monday, August 4, 2025. The activity was attended by 14 teachers from several schools in Bendung Village. The speaker was Kusrinawati, S.Si., who serves as the Coordinator of Curriculum and Assessment for Elementary Schools at the Department of Education and Culture of Serang Regency. The seminar results indicated an increase in teachers’ understanding of using Canva, Quizizz, and various national educational platforms. Teachers also gained insights into the implementation of AI in elementary schools, the introduction of coding, and the development of technology-based extracurricular programs. This activity also strengthened collaboration among teachers, the local Department of Education, and KKM students, thereby contributing to sustainable improvements in the quality of education.